Role of external ventricular drainage in the management of intraventricular hemorrhage; its complications and management - Kirmani, Altaf Rehman (Surg Neurol Int, 2015)
BACKGROUND: External ventricular drainage (EVD) is the procedure of choice for the treatment of acute hydrocephalus and increased intracranial pressure in patients of subarachnoid hemorrhage (SAH) and intracerebral hemorrhage with hydrocephalus and its sequelae. We evaluated the use of EVD in patients of SAHs (spontaneous/posttraumatic with/without hydrocephalus), hypertensive intracerebral bleeds with interventricular extensions, along with evaluation of the frequency of occurrence of complications of the procedure, infectious and noninfectious, and their management. METHODS: During the period of 2½ years, between September 2012 and February 2015, 130 patients were subjected to external drainage procedure and were prospectively enrolled in this study. Information was collected on each patient regarding age, sex, diagnosis, underlying illness, secondary complications, other coexisting infections, use of systemic steroids, antibiotic treatment (systemic and intraventricular), and whether any other neurosurgical procedures were performed within 2 weeks of EVD insertion or any time the duration of ventriculostomy. RESULTS: The study population of 130 patients underwent a total of 193 ventriculostomies. Thirty-six patients had ventriculostomy infection (27.6%). Evaluation of the use of EVD was done by comparing preoperative and postoperative grading scores. Forty-nine patients survived and improved their score from Grade 3–5 to Grade 2–4. Twenty-nine patients were moderately disable, 16 were severely disable, and 5 were left in the vegetative state. Evaluation of outcome of patients revealed that there was an overall mortality of 61 (46.9%) patients both in the acute phase and later. 33 of the 39 patients having Glasgow Coma Score (GCS) 3–5 at the time of EVD insertion expired, as against 20 of the 51 patients in GCS 6–8. Patients in GCS 9–12 had an even better outcome, with 8 of the 35 patients in this group expiring. CONCLUSIONS: The use of EVD should be undertaken only in situation where it is absolutely necessary and ventriculostomy should be kept only for the duration required, and this should be monitored on a daily basis, given the exponential increase in infection after 5 days.